2016
DOI: 10.4103/0976-500x.184770
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing adherence to anti-craving medications and drinking outcomes in patients with alcohol dependence: A hospital-based study

Abstract: Objective:To examine the factors influencing the pattern and extent of anti-craving medication adherence and drinking outcomes in alcohol-dependent patients.Materials and Methods:Demographic data from 102 inpatients were collected at discharge from hospital. The pattern of anti-craving medication, extent of adherence, and drinking outcome was collected at 1st, 3rd, 8th, and 12th week follow-up. Patients’ self-reported adherence, medication diary, and simplified medication adherence questionnaire were used and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…The percentage of patients who were adherent in each group was exceptionally high for an alcohol pharmacotherapy trial. Depending on the definition of medication adherence, rates of medication adherence range from a low of 20% to a high of 80% (Lohit, 2016); results of the current study show a medication adherence rate of over 90%.…”
Section: Discussionmentioning
confidence: 70%
“…The percentage of patients who were adherent in each group was exceptionally high for an alcohol pharmacotherapy trial. Depending on the definition of medication adherence, rates of medication adherence range from a low of 20% to a high of 80% (Lohit, 2016); results of the current study show a medication adherence rate of over 90%.…”
Section: Discussionmentioning
confidence: 70%
“…[3132] A recent study reported that decrease in adherence to acamprosate and naltrexone was associated with significantly higher relapse rate and decreased abstinence. [33] There have been controversial findings regarding lack of efficacy of acamprosate and naltrexone. One retrospective chart review from India found no significant difference in abstinence rates between the patients receiving acamprosate and naltrexone.…”
Section: Discussionmentioning
confidence: 99%
“…First, lack of randomized controlled trials with blinding is of the most important methodological flaws. The studies have largely been cross-sectional as well as prospective-observational studies[72633464748] and retrospective chart reviews. [20214950] There were few randomized open-labeled trials.…”
Section: Discussionmentioning
confidence: 99%
“…50 Despite the above, XR-NTX in a primary care setting has significantly shown to be more effective, feasible, and cost-effective than O-NTX. 51 Furthermore, for patients with comorbid opioid misuse who are in treatment for AUD, XR-NTX could enhance treatment adherence. 27 Barriers to adherence in people with AUD included younger age, self-decision, emotional factors, adverse events greater drinking severity, dissatisfaction with the treatment and session frequency and lack of perceived benefit.…”
Section: Adherence and Predictorsmentioning
confidence: 99%